Autonomous Learning in Higher Education: An Iraqi EFL Students’ Perceptions - Ranjbar, Mohammad Hossein; Nasiri, Sara Fatemeh (Universal Education, 2024)
This study investigates the perceptions of Iraqi EFL (English as a Foreign Language) students regarding autonomous learning (AL) and its impact on their academic development. With the increasing importance of English for communication, education, and career prospects in a globalized world, understanding students' views on AL is critical, especially in Iraq, where traditional, teacher-centered pedagogies dominate. The research employs a survey method, gathering data from 359 EFL students across six universities in Iraq. The questionnaire addresses various aspects of AL, including perceptions, benefits, challenges, independence in learning management, and the role of the teacher. The findings indicate that Iraqi students generally view AL positively, with high scores for motivation, goal-setting, and critical thinking, underscoring the value of learner autonomy. Benefits such as improved problem-solving skills and deeper engagement with course material were frequently mentioned. However, challenges such as difficulty in self-motivation and the lack of social support were also highlighted. Additionally, students expressed a desire for more structured teacher involvement in guiding their autonomous learning efforts. This study concludes that while AL significantly enhances student independence and learning outcomes, the success of AL initiatives in Iraqi higher education depends on providing sufficient support, motivation, and resources for students. The research also emphasizes the need for teachers to play a facilitative role in the AL process. The findings contribute valuable insights into how AL can be adapted to meet the specific needs and challenges of Iraqi EFL learners, offering a foundation for future educational reforms in the region.